Patriarki Sebagai Akar Diskriminasi Gender di Sri Lanka - Bayu Setyawan (Resolusi: Jurnal Sosial Politik, 2020)
In the last few decades, women in Sri Lanka still face social inequality. This paper highlights that patriarchy as a socio-cultural factor is very dominant in gender discrimination in the country. Among them is the role of religion which has created the root of male tendency to dominance. As a result, women become a marginalized group, including in politics and work. This disparity has in fact been rooted from the family level, where the role of women in various matters in this small scope is very limited.